IMPROVING LEARNING APPLICATION ON EXPOSITION TEXT MATERIALS TO IMPROVE LEARNING OUTCOME OF STUDENTS OF CLASS X TPM 2 SMK NEGERI 1 PUNGGING MOJOKERTO - IM. SHOFI’I (Jurnal Scientia, 2022)
The purpose of this study was to determine the improvement of student learning outcomes in class X TPM 2 SMK Negeri 1 Pungging Mojokerto Regency through the application of the IMPROVE model to the exposition text material. This research is a classroom action research with 2 cycles of improvement which includes the stages of planning, implementation, observation and reflection. The action given is to apply the IMPROVE model to the exposition text material. The research was conducted in August 2022 in class X TPM 2 SMK Negeri 1 Pungging. The results showed that (1) the implementation of the lesson plans showed that the lesson plans could be implemented well, (2) the student activities showed student centered learning and students were very enthusiastic about listening to the information conveyed by the teacher, (3) student responses after the implementation the IMPROVE model used shows a positive response, and (4) the mastery learning outcomes in the first cycle individually have been achieved and classically have not been achieved, while in the second cycle the mastery learning outcomes both individually and classically have been achieved.